Sensorless fuzzy direct torque control of induction motor with sliding mode speed controller. (December 2021) - El Daoudi, Soukaina; Lazrak, Loubna; El Ouanjli, Najib; Ait Lafkih, Mustapha
Highlights: Design of a direct torque control based on fuzzy logic to control the asynchronous motor is introduced. External loop speed regulation is provided by a sliding mode controller. Stator flux model reference adaptive system is used to ensure a highly precise sensorless motor control. Critical analysis of different simulations performances is carried out under several operating constraints. The proposed control methods are evaluated in terms of ripples, overshoot, undershoot and response time. Abstract: In this work, a fuzzy direct torque control (DTC) is developed for asynchronous motor drive powered by two-level inverter. The main objective is to enhance the system performance by reducing electromagnetic torque and stator flux ripples while improving stator current waveforms. The hysteresis comparators and voltage vector switching table of classic DTC are replaced by fuzzy logic block to ensure robust control against various disturbances. The outer speed loop is initially executed by PI regulator and secondly by sliding mode controller, for both systems stator flux MRAS estimator is adopted. A critical and comparative study between the DTC based on fuzzy logic and non-linear sliding mode DTC was done under MATLAB/SIMULINK. The performance analysis was carried out under different operating conditions such as steady and transient states, low, medium and high speeds, speed reversal and application of two different loads at various times.